2020
DOI: 10.1007/s10029-020-02291-7
|View full text |Cite
|
Sign up to set email alerts
|

Transrectus sheath pre-peritoneal (TREPP) procedure versus totally extraperitoneal (TEP) procedure and Lichtenstein technique: a propensity-score-matched analysis in Dutch high-volume regional hospitals

Abstract: Purpose Results of the most commonly used inguinal hernia repair techniques often originate from expert centers or from randomized controlled studies. In this study, we portray daily-practice results of a high-volume, regional surgical group in the Netherlands, comparing TREPP (open (posterior) transrectus sheath pre-peritoneal) with Lichtenstein (open anterior) and TEP (endoscopic (posterior) totally extraperitoneal). We hypothesize that the TREPP shows more favorable outcome compared to the current gold stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…With a 1b level of evidence (LoE), 23 this trial is the first to confirm the earlier published promising results after TREPP 8 12 and good results after TIPP surgery. 4 , 5 Retrospective TREPP studies report CPIP rates of 1.7% 10 and 5.3% 9 (LoE 3b-4) and recurrence rates of 1.2%, 9 1.7% 10 and 3.9% 11 (LoE 3b-4) with significant follow-up variation (2 weeks–2 years). The more extensive evidence on TIPP surgery, mainly compared to Lichtenstein's technique, shows <5% CPIP rates (LoE 1b–2b), 4 , 5 , 24 26 ∼3% recurrence rates (LoE 1b-2b), 4 , 5 , 24 , 25 , 27 and quicker recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a 1b level of evidence (LoE), 23 this trial is the first to confirm the earlier published promising results after TREPP 8 12 and good results after TIPP surgery. 4 , 5 Retrospective TREPP studies report CPIP rates of 1.7% 10 and 5.3% 9 (LoE 3b-4) and recurrence rates of 1.2%, 9 1.7% 10 and 3.9% 11 (LoE 3b-4) with significant follow-up variation (2 weeks–2 years). The more extensive evidence on TIPP surgery, mainly compared to Lichtenstein's technique, shows <5% CPIP rates (LoE 1b–2b), 4 , 5 , 24 26 ∼3% recurrence rates (LoE 1b-2b), 4 , 5 , 24 , 25 , 27 and quicker recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Other TREPP principles are: an open technique with a non-fixated preperitoneal mesh based on the biomechanical upstream principle. 8 Previous retrospective studies were promising [8][9][10][11][12] and contributed to the hypothesis of the ENTREPPMENT trial that less patients would suffer from CPIP after TREPP compared to TIPP.…”
mentioning
confidence: 99%
“…It has the advantages of a short operation time, low recurrence rate, flat learning curve and ease of mastery. In addition, the Lichtenstein method can be performed under local anaesthesia, which is more suitable for high‐risk patients and has irreplaceable advantages 6 . The classic Lichtenstein method uses non‐absorbable sutures to fix the mesh 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Lichtenstein method can be performed under local anaesthesia, which is more suitable for high-risk patients and has irreplaceable advantages. 6 The classic Lichtenstein method uses non-absorbable sutures to fix the mesh. 7 A related study has shown that suture fixation may increase the risk of chronic postoperative inguinal pain (CPIP).…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating TREPP/OPP have thus far been limited, but some single-institution observational studies have shown promising outcomes [10][11][12][13]. Comparisons of TREPP to MIS TEP and open Lichtenstein approaches demonstrate no significant differences in recurrence rates, postoperative complications, or postoperative pain [5,14], and a recent meta-analysis on TREPP demonstrated low risk of recurrence, chronic pain, hematoma, and wound infection [15]. While evaluation of the quality of hernia repair has traditionally involved comparison of recurrence rates, patients themselves also measure the success of their surgery by their quality of life in recovery.…”
Section: Introductionmentioning
confidence: 99%